Ensuring Quality Transitions From Early Years’ Establishments Into Primary Schools: Putting Research Into Practice - Moir, Taryn; Johnson, Jayne (Frontiers in Psychology, 2021)
Preschool to primary school transitions can be a time of anxiety for pupils, parents, and practitioners. The purpose of this study was to investigate what should be in place to support transitions and develop a shared understanding of what constitutes a nurturing transition for children. It is hoped that sharing this across service providers will increase consistency of practice. The design took a flexible qualitative approach to ensure the co-creation of shared meaning. Following an initial exploratory activity using a Person Centered Planning (PCP) approach, four qualitative activities were identified. Early years’ staff, primary teachers, parents, and pupils were recruited as participants from within a Scottish local authority to take part in these collaborative activities with qualitative and quantitative components, which enabled the co-construction of a transition timeline that articulates the core activities needed for optimal early years’ centers (EYC) to primary transitions. This timeline outlines various preparatory activities that can be taken for all pupils and also those with identified additional support needs (ASNs). In addition, examples of excellence were identified. While this document illustrates examples of good practice, it is not meant to replace other existing positive transition work; rather it is a guide that can enhance existing procedures within any given context.